Developing digital platform to increase the sales of MSME in Kalakijo, Bantul, Yogyakarta - Rela Adi Himarosa; Muhammad Budi Nur Rahman; Rizky Nuryani; Fajar Sofyantoro (Community Empowerment, 2022)
The tourism village of Kalakijo, Yogyakarta, promotes batik and traditional culinary ‘ingkung’ as its main branding strategy. To date, the marketing and promotion of Kalakijo are performed based on conventional strategies. The emergence of the pandemic in recent years further complicates the problems faced by micro, small, and medium enterprises (MSME) owners in Kalakijo. This program aimed to assist the development and application of digital marketing strategies to increase the reach of promotions and attract the interest of younger generations in batik and ingkung. Prior to program implementation, surveys and discussions with Kalakijo villagers and business owners were carried out. The programs were implemented in several steps, including strengthening brand identity, building websites, making product catalogs, and setting up e-commerce platforms. Evaluation and monitoring were also carried out regularly during the program implementation. Through this program, MSMEs in Kalakijo are able to become entity that are independent, adaptive, and competitive in the digital era.